Characterisation of Catfish (Clarias batrachus) Waste Oil: γ-Cyclodextrin Inclusion Complex - Abdul Haiyee, Zaibunnisa; Izzatul Adyani Yahya, Nor; Abd Rashid, Norizzah; Mohd Nor, Norakma; Mat Hashim, Dzulkifly (International Journal of Engineering and Technology, 2018)
Catfish is a cheap source of essential omega-3 fatty acids especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). In this study, catfish waste oil was extracted and clean-up using pressurised liquid extraction (PLE) from viscera of catfish (Clarias batrachus). However, the characteristics of catfish waste oils are sticky, strong fishy odour, easily oxidised with short shelf-life. Catfish waste oil was converted into powder by formation of inclusion complex with γ–cyclodextrin. Inclusion complex was prepared by using co-precipitation and kneading methods and compared with physical mixture. The inclusion complex formed were characterised by using Field Emission Scanning Electron Microscopy (FESEM), Differential Scanning Calorimeter (DSC) and Fourier Transform Infrared Spectroscopy (FTIR. Results from FESEM images revealed that formation of inclusion complex using co-precipitation and kneading methods has smaller in crystal sizes and appeared as different morphology compared to physical mixture. DSC proved that co-precipitation method was able to formed new solid phase due to shifting of melting point to the higher temperature (130 ºC). FTIR supported the result by reduction of intensity of C-H band in co- precipitation which results a formation new solid phase. Therefore, co-precipitation method was able to successfully produce inclusion complex of catfish oil: γ-cyclodextrin.
Keywords: catfish oil; Î³-cyclodextrin; co-precipitation; kneading; physical mixture.